Analisis Konsep Pendidikan Kritis Tan Malaka Dalam Buku Aksi Massa: Pendidikan Sebagai Alat Perjuangan - Syiva Al Salwa; Istikhomah Istikhomah; Jessica Nur Faeda; Stanny Tessa Yuriska (Pusat Studi Pancasila dan Kebijakan Universitas 17 Agustus 1945 Banyuwangi, 2025)
This study examines Tan Malaka's thoughts on criticaleducation as expressed in his work Aksi Massa (1926), with anemphasis on his view of education as an instrument of politicalstruggle and national liberation. For Tan Malaka, education isnot neutral, but rather laden with ideological interests, whereduring the colonial period it was used as a tool by the colonizersto produce a skilled workforce that was politically obedient. From a critical education perspective, Tan Malaka's ideasemphasize the importance of education as a means of buildingclass consciousness, strengthening solidarity, and mobilizingworkers and farmers towards true independence. This study uses a qualitative method with a literature study approach thatfocuses on Aksi Massa and secondary sources relevant tocritical education. The findings show that for Tan Malaka, education not only functions as an intellectual activity, but alsoas a medium for liberation and mass organization to destroyoppressive structures in order to realize a just and independentsociety.